Direction of Trade Statistics, September 2015. (Direction of Trade Statistics; September 2015, 2015)
This August 2015 issue of Direction of Trade Statistics (DOTS) Quarterly provide, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. The quarterly issues, yearbook, and CD-ROM of the DOTS present, for most member countries of the IMF, current figures on the value of merchandise exports and imports disaggregated according to their most important trading partners. Estimation occurs if a reporting country does not report trade with its partners for a specific period. Data are estimated for all partners and not for some of the partners. In the absence of some or all the monthly DOTS, quarterly or annual reported DOTS are used. When information is not reported and is inadequate to support the estimation techniques, the data are extrapolated using a matrix of trade among broad country groups.